Vietnam education in development process of digital society - Nguyễn Hải Hoàng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The explosion of industrial revolution 4.0 has impacted and gradually changed production and business activities as well as other areas of social life; digital society was born as a necessity. So how does education need to change? That is the content that the author wants to mention in this article.